Association between traffic-related air pollution and asthma in preschool children in a national Japanese nested case–control study. Issue 2 (25th February 2016) - Hasunuma, Hideki; Sato, Tosiya; Iwata, Tsutomu; Kohno, Yoichi; Nitta, Hiroshi; Odajima, Hiroshi; Ohara, Toshimasa; Omori, Takashi; Ono, Masaji; Yamazaki, Shin; Shima, Masayuki
Abstract : Objectives: There has been little study on the effect of traffic-related air pollution on the incidence and persistence of asthma in preschool children. We evaluated the association of exposure to traffic-related air pollution with the incidence/persistence of asthma during the first 3 years of life using a population-based study. Methods: A baseline survey was conducted in 1½-year-old children (n=63 266). A follow-up survey at 3 years of age (n=43 343) identified new-onset asthma cases (n=853) and persistence of asthma (n=214). In the prevalence/persistence study, the outdoor concentrations of nitrogen oxides (NOx) and elemental carbon (EC) at home during the first 1½ years of life were estimated by a dispersion model. In the nested case–control study, which regarded incidence of asthma as cases, the personal exposure levels were estimated by dispersion model including time-activity pattern. Results: There was no statistically significant association between the incidence of asthma between age 1½ and 3 years and personal exposure levels to NOx nor EC. However, the persistence of asthmatic symptoms (between 1½ and 3 years) was significantly associated with outdoor concentrations of NOx. ORs for the persistence of asthmatic symptoms were 6.02 (95% CI 1.51 to 23.92) for the comparison between the upper 5th and lower 25th centiles of NOx. Conclusions: While no statistically significant association was observed for the incidence of asthma, the persistence of asthmatic symptoms in preschool children was significantly associated with traffic-related air pollution. This supports its importance as a risk factor in childhood airway disease.